Party positions over international human rights treaties in the United States in the Post-Cold War - Contrera, Flávio [UNESP]; Hebling, Matheus Lucas (Pontificia Universidade Catolica de Minas Gerais, 2021)
This article aimed to verify the occurrence of convergence and congruence in the positions that the Democratic and Republican parties express about human rights treaties in the Electoral, in the Executive, and the Legislative arenas, in the Post-Cold War (1992-2016). The use of the comparative method guided the study of six specific cases, analyzed using qualitative techniques. The results point to two trends. The first is that the possibility of convergence between the Democratic and Republican parties tends to diminish when their positions on human rights treaties are anchored by ideological perspectives, and the second is that a party’s position on a treaty tends to be congruent among political arenas. Moreover, the divergence of positions between the parties clarifies the liberal internationalist character of the Democratic positions and the conservative isolationist approach of the Republican positions.
Posições partidárias sobre tratados internacionais de direitos humanos nos Estados Unidos no pós-Guerra Fria
Posiciones partidistas sobre los tratados internacionales de derechos humanos en los Estados Unidos después de la Guerra Fría
Keywords: Human rights; Political parties; Post-cold war; The United States; Treaties